Environmental Lead Exposure Accelerates Progressive Diabetic Nephropathy in Type II Diabetic Patients. (27th February 2013) - Huang, Wen-Hung; Lin, Ja-Liang; Lin-Tan, Dan-Tzu; Hsu, Ching-Wei; Chen, Kuan-Hsing; Yen, Tzung-Hai
Abstract : Whether environmental lead exposure has a long-term effect on progressive diabetic nephropathy in type II diabetic patients remains unclear. A total of 107 type II diabetic patients with stage 3 diabetic nephropathy (estimated glomerular filtration rate (eGFR) range, 30–60 mL/min/1.73 m 2 ) with normal body lead burden (BLB) (<600 μ g/72 hr in EDTA mobilization tests) and no history of exposure to lead were prospectively followed for 2 years. Patients were divided into high-normal BLB (>80 μ g) and low-normal BLB (<80 μ g) groups. The primary outcome was a 2-fold increase in the initial creatinine levels, long-term dialysis, or death. The secondary outcome was a change in eGFR over time. Forty-five patients reached the primary outcome within 2 years. Although there were no differences in baseline data and renal function, progressive nephropathy was slower in the low-normal BLB group than that in the high-normal BLB group. During the study period, we demonstrated that each 100 μ g increment in BLB and each 10 μ g increment in blood lead levels could decrease GFR by 2.2 mL/min/1.72 m 2 and 3.0 mL/min/1.72 m 2 (P = 0.005 ), respectively, as estimated by generalized equations. Moreover, BLB was associated with increased risk of achieving primary outcome. Environmental exposure to lead may have a long-term effect on progressive diabetic nephropathy in type II diabetic patients.